STRATEGI PENGELOLAAN PERPUSTAKAAN DIGITAL UNTUK MENINGKATKAN PELAYANAN PRIMA DI PERGURUAN TINGGI - Jannah, Robbiyatul; Wijayati Wardoyo, Dewie Tri; Kistyanto, Anang (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
Technological advancements highlight the urgent need for digital library management to support the quality of higher education services. This study aims to analyze the management strategies of digital libraries at the Faculty of Education, Universitas Negeri Surabaya (FIP UNESA), in enhancing service excellence. A descriptive qualitative approach with a holistic single case study method was employed. The findings reveal that implementing well-planned management, developing technological infrastructure, providing continuous training, and conducting user feedback-based evaluations positively affect service efficiency and user satisfaction. However, limitations in human resources and insufficient librarian training remain significant obstacles. The study concludes that continuous training and improvement of human resource competencies are crucial factors in delivering optimal digital library services.